EFEKTIVITAS PENGATURAN BATAS USIA PERKAWINAN DI KANTOR URUSAN AGAMA KOTA PALEMBANG - Elsa Manora; Eti Yusnita; Yusida Fitriyati (Program Studi Al-Ahwal Al-Syakhshiyyah, 2022)
Marriage is a bond between a man and a woman who unite and complement each other to live as husband and wife in a marriage bond. Along with the times, the government issued new regulations relating to the minimum age limit for marriage in Law Number 16 of 2019 Article 7 Paragraph (1) Amendment to Law Number 1 of 1974 concerning Marriage. This study aims to examine the effectiveness of setting the marriage age limit after Law No. 16 of 2019 has been implemented at the Palembang City Religious Affairs Office. The research method used is the empirical normative juridical method with the type of field research (field research). Based on the results of the study, the authors concluded that the effectiveness of setting the age limit for marriage after Law Number 16 of 2019 at the Palembang City Religious Affairs Office had been carried out well for several reasons as evidenced by each religious affairs office, namely because of the parties involved. the parties concerned both from the Ministry of Religion and from the Office of Religious Affairs have complied with the regulations as stated in the Circular from the Ministry of Religion regarding the enactment of Law Number 16 of 2019. The factors that influence its effectiveness are the important roles of the Office of Religious Affairs in carrying out their duties and socializing the Law. Keywords: Effectiveness; Marriage Age Limit; Law Number 16 Year 2019